Click chemistry: 1,2,3-triazoles as pharmacophores - Agalave, Sandip G.; Maujan, Suleman R.; Pore, Vandana S. (Chemistry-an Asian Journal, 2011)
The copper(I)-catalyzed 1,2,3-triazole-forming reaction between azides and terminal alkynes has become the gold standard of `click chemistry' due to its reliability, specificity, and biocompatibility. Applications of click chemistry are increasingly found in all aspects of drug discovery; they range from lead finding through combinatorial chemistry and target-templated in vitro chemistry, to proteomics and DNA research by using bioconjugation reactions. The triazole products are more than just passive linkers; they readily associate with biological targets, through hydrogen-bonding and dipole interactions. The present review will focus mainly on the recent literature for applications of this reaction in the field of medicinal chemistry, in particular on use of the 1,2,3-triazole moiety as pharmacophore.
Keywords: Click chemistry; Copper; Cycloaddition; pharmacophores; triazoles

Alumina-supported copper iodide: an efficient and recyclable catalyst for microwave-assisted synthesis of 1,4-disubstituted 1,2,3-triazoles via three-component reaction in water - Agalave, Sandip G.; Pharande, Shrikant G.; Gade, Swapna M.; Pore, Vandana S. (Asian Journal of Organic Chemistry, 2015)
A one-pot procedure for the synthesis of 1,4-disubstituted 1,2,3-triazoles by a three-component reaction of allyl or benzyl halides, sodium azide, and terminal alkynes over a neutral alumina-supported copper iodide catalyst has been developed. The products were isolated by simple filtration followed by washing of the catalyst with acetone. The products were obtained in almost pure form in up to 98% yield (TON 495). The catalyst can be recycled for more than eight subsequent reactions. The halides are directly converted into triazoles via in situ formation of azides and thus handling of hazardous azides can be avoided. The broad scope of this protocol is shown by the synthesis of a variety of diversely substituted 1,2,3-triazoles and also two-component azide-alkyne click reaction. The key features of this procedure are the use of water as a solvent, recyclability of the catalyst up to eight runs without appreciable loss of activity, and high yields of products. The catalyst has been fully characterized by FTIR, solid-state NMR and EDX spectroscopy, ESEM, TGA, and XRD.
Keywords: 1; 2; 3-triazoles; 4; copper(I) iodide; Cycloaddition; disubstituted 1; Microwave chemistry; supported catalysts

Design and synthesis of 11 alpha-substituted bile acid derivatives as potential anti-tuberculosis agents - Pore, Vandana S.; Divse, Jaisingh M.; Charolkar, Chaitanya R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2015)
We have synthesized a series of novel 11 alpha-triazoyl bile acid derivatives. In addition, we also have synthesized N-alkyl and N-acyl derivatives of C-11 amino bile acid esters. All the compounds were evaluated for the inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) at 30 mu g/mL level. Four lead compounds (2b, 3, 7 and 8) were further confirmed from their dose dependent effect against MTB. These compounds were found to be active against Dormant and active stage MTB under both in vitro as well as within THP1 host macrophages. The most promising compound 2b showed strong antitubercular activities against MTB under in vitro and ex vivo (IC90 value of similar to 3 mu g/mL) conditions and almost insignificant cytotoxicity up to 100 mu g/mL against THP-1, A549 and PANC-1 human cancer cell lines. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies of these compounds into the active site of DprE1 enzyme revealed a similar binding mode to native ligands in the crystal structure thereby helping to establish a structural basis of inhibition of MTB. The synthesized compounds were analyzed for ADME properties and showed potential to develop good oral drug candidates. Our results clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Antituberculosis; Bile acids; Cycloaddition; Docking study; In silico ADME